Proposta de aplicativo “PuerpérioSEGURO” em plataforma mobile como tecnologia para o cuidado à beira leito - (:unkn) unknown (Universidade Federal do Amazonas, 2020)
Mobile applications have stood out as innovative auxiliary technologies to nursing care in recent years. This study aimed to propose an application on a mobile platform as a health technology for immediate / mediate care to the puerperal woman at the bedside. The study is characterized as a methodological technological innovation, carried out from August 2018 to July 2020, in three stages: integrative literature review; development of mobile technology architecture according to the principles of software engineering, using JAVA programming and SDK package for Android system; and validation of mobile technology by nursing and computing judges. Two online forms were used via Google Forms with Likert scale, directed to the group of nurses who evaluated the aspects of functionality, reliability, usability and efficiency of the application, and to the computer group, which in addition to the aspects already mentioned, evaluated the maintenance requirements and technology portability. The data were stored in Microsoft Office Excel 360® 2019 for processing, and for the analysis of the Content Validity Index, the computing resources of the SPSS version 22.0 system were used in a Windows 10 environment. Data collection was authorized by the Research Ethics at the Federal University of Amazonas (no 4,025,402). The literature review consisted of 24 studies, most with evidence level 4 (22 studies), distributed by technological classification: Leve (5), Leve-Dura (12) and Dura (7), not being identified in the platforms Android and iOS application same or similar to the one developed in this study. The prototype of the PuerpérioSEGURO application was developed, being registered in the Registro de Obras under number 610144519, which has its content organized in 5 main interfaces, namely: Login - the registration takes place; Menu - guidance on the application and error notification, flow chart, terms of use and references; New Assessment and Reevaluation - Registration of puerperal women, physical examination of the mother-child binomial directed, care plan and daily clinical summary; and Archive - database with clinical summaries of clients who were discharged from the maternity hospital. In the validation, eight doctor nurses formed the Interface Judges group, all professors from public or private institutions and with notable experience in the field of obstetrics and health technologies, presenting the following agreement results Totally Agree + Partially Agree: functionality (100.0 %); reliability (100.0%), usability (100.0%) and efficiency (100.0%), with an overall Content Validity Index of 100.0%. The Judges of the System group was composed of a master and seven doctors in computer science, all professors from public or private institutions and with notable experience in the field of applications and technologies in health, presenting the following results of agreement Totally Agree + Partially Agree: functionality (91.67%); reliability (81.25%), usability (100.0%); efficiency (100.0%); maintainability (91.67%); and portability (87.50%), with an overall Content Validity Index of 92.96%. The developed technology is innovative and obtained a Content Validity Index considered of excellence, being able to be tested in later studies by the target audience for which it is intended.
Keywords: Enfermagem - Processamento de dados; Enfermagem obstétrica; Puerpério; CIÊNCIAS DA SAÚDE: ENFERMAGEM; Tecnologias em Saúde; Informática em Enfermagem; Aplicativos; Saúde da Mulher; Período Pós-Parto